Molecular and Clinical Characterization of UBE2S in Glioma as a Biomarker for Poor Prognosis and Resistance to Chemo-Radiotherapy - Hu, Li; Cheng, Xingbo; Binder, Zev; Han, Zhibin; Yin, Yibo; O’Rourke, Donald M.; Wang, Sida; Feng, Yumeng; Weng, Changjiang; Wu, Anhua; Lin, Zhiguo (Frontiers in Oncology, 2021)
Glioblastoma is the most common and lethal brain cancer with various molecular and clinical characteristics. UBE2S has been reported to have high expression in many cancers. But its expression in gliomas, as well as the potential correlation with clinical outcome, remains unknown. We obtained RNA sequencing data of 325 glioma samples from the Chinese Glioma Genome Atlas and The Cancer Genome Atlas. 114 cases of glioma tissue (WHO grades II-IV) samples were used for protein expression assays. Then, the molecular and biological characteristics, and the clinical prognostic value of UBE2S were analyzed. We found that UBE2S expression was associated with a higher grade of glioma and PTEN mutations. In addition, UBE2S was correlated with glioma malignancy and chemo-radiotherapy resistance and predicted worse survival for LGG patients as an independent indicator. Furthermore, we identified five UBE2S ubiquitination sites and indicated that UBE2S associated with Akt phosphorylation in glioblastoma malignancy. Our results implied that UBE2S expression was negatively correlated with 1p19q loss and IDH1 mutation while positively correlated with epidermal growth factor receptor amplification and PTEN mutation. Our study revealed UBE2S expression strongly correlated with glioma malignancy and resistance to chemo-radiotherapy, may serve as a crucial biomarker for a poor prognosis.